Possible Binding Modes Of Withaferin-A And Its Analogs In The Active Site Of Nnos Molecular Docking Studies - ZAVED AHMED KHAN; ASIT RANJAN GHOSH (International Journal of Pharma and Bio Sciences, 2011)
Docking simulations were carried out with AutoDock 3.0, using the withaferin-A bound to nNOS (PDB ID: 3JWT) to define the binding pocket. The appropriate ligand targets were built in SYBYL 6.8 by modifying the molecular structure of withaferin-A which was extracted from the crystal structure. The withanolides 1–3 and 4–5 were formed using SYBYL program<a href="http://www.sciencedirect.com/science?_ob=ArticleURL&_udi=B6WBK-4GHBMB3-1&_user=2968410&_coverDate=08%2F19%2F2005&_rdoc=1&_fmt=high&_orig=gateway&_origin=gateway&_sort=d&_docanchor=&view=c&_acct=C000059350&_version=1&_urlVersion=0&_userid=2968410&md5=155a899ab632d75079748efdd32ecaca&searchtype=a#bbib23">[23] K. Stains, SYBYL molecular modeling software. Tripos Associate Ltd., St. Louis, MO, 1999.(. Molecular docking study revealed that all the ligands are completely buried inside the aromatic gorge of nNOS, while compounds 1, 3, and 5 extend up to the catalytic triad. A comparison of the docking results showed that all ligands generally adopt the same binding mode and lie parallel to the surface of the gorge. The superposition of the docked structures demonstrated that the non-flexible skeleton of the ligands always penetrates the aromatic gorge through the six-membered ring A, allowing their simultaneous interaction with more than one subsite of the active center. The affinity of ligands with nNOS was found to be the cumulative effects of number of hydrophobic contacts and hydrogen bonding. The nNOS inhibitory potential could make compounds 1–5 possible drug candidates for further study to treat anxiety and associated problems.